Regenerative medicine for the treatment of chronic low back pain: a narrative review. Issue 2 (February 2023) - Wang, Fengfeng; Cheung, Chi Wai; Wong, Stanley Sau Ching
Low back pain (LBP) is a common and important clinical problem. In addition to pain, patients are also affected by personal, social, and economic burdens. Intervertebral disc (IVD) degeneration is a common cause of LBP, further increasing the patient's morbidity and medical costs. The limitations of current treatment strategies for long-term pain relief mean that increasing attention has been paid to regenerative medicine. We carried out a narrative review to explore the roles of four types of regenerative medicine for treating LBP: marrow-derived stem cells, growth factors, platelet-rich plasma, and prolotherapy. Marrow-derived stem cells are regarded as an ideal cell source for IVD regeneration. Growth factors may stimulate the synthesis of extracellular matrix and attenuate or reverse the degenerative process in IVD, while platelet-rich plasma, which contains multiple growth factors, is thought to be a promising alternative therapy for IVD degeneration. Prolotherapy can initiate the body's inflammatory healing response to repair injured joints and connective tissues. This review summarizes the mechanisms, in vitro and in vivo studies, and clinical applications of these four types of regenerative medicine in patients with LBP.